2009
DOI: 10.1021/jp904806f
|View full text |Cite
|
Sign up to set email alerts
|

A Kirkwood−Buff Derived Force Field for Thiols, Sulfides, and Disulfides

Abstract: A force field has been developed for molecular simulations of methanethiol, dimethyl sulfide, and dimethyl disulfide mixtures. The force field specifically attempts to balance the solvation and self-association of these solutes in solution mixtures with methanol. The force field is based on the Kirkwood–Buff (KB) theory of solutions and is parametrized using the KB integrals obtained from the experimental activity coefficients for the solution mixtures. The transferability of the force field was tested and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
(115 reference statements)
1
36
0
Order By: Relevance
“…81,91,94,[96][97][98][99][100][101] The results showed that without introducing polarization good agreement with experimental KB data can be obtained. The present study demonstrated that the polarizable Drude force field, which was not developed by targeting experimental KB data, can also achieve almost the same degree of accuracy compared to KBFF, except for activity derivative and excess Gibbs free energy, which will be the focus in our future force field optimization efforts.…”
Section: Discussionsupporting
confidence: 55%
“…81,91,94,[96][97][98][99][100][101] The results showed that without introducing polarization good agreement with experimental KB data can be obtained. The present study demonstrated that the polarizable Drude force field, which was not developed by targeting experimental KB data, can also achieve almost the same degree of accuracy compared to KBFF, except for activity derivative and excess Gibbs free energy, which will be the focus in our future force field optimization efforts.…”
Section: Discussionsupporting
confidence: 55%
“…Details of the force fields are provided elsewhere. [28][29][30][31] All mixtures were simulated with enough molecules to occupy a cubic box of length of Ϸ6 nm, starting from random initial configurations, and were simulated for between 10 and 20 ns.…”
Section: Methodsmentioning
confidence: 99%
“…Similar trends are observed for mixtures of TOL/MOH, MSH/ MOH, and MSM/MOH. 29,30 Mixtures of BEN/TOL and, to some extent, MSH/MSM would be expected to display close to ideal behavior. In contrast, the behavior of BEN/MSH mixtures would be more difficult to predict using basic chemical principles.…”
Section: Molecular Dynamics Simulations Of Symmetric Ideal Solutionsmentioning
confidence: 99%
“…More details can be found in our recent studies [27,28]. All mixtures are simulated via classical molecular dynamics techniques using the Gromacs program (version 3.3) [29].…”
Section: Simulation Detailsmentioning
confidence: 99%